2006
DOI: 10.1007/s00432-006-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phosphorylated ERK1/2 and homeodomain protein CDX2 in cholangiocarcinoma

Abstract: These results imply that pERK1/2 may be important for the differentiation of tubular-type CCA, while CDX2 is related to the intestinal phenotype of papillary-type CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…COX-2 and p-ERK1/2 expression were found to be markedly lower in normal gallbladder tissues than in GBC tissues, and their expression levels were also lower in HIBEpiC cells than in GBC-SD and NOZ cells. These results were consistent with previous studies (9)(10)(11), indicating that aberrant COX-2 and ERK1/2 activation may serve key roles in GBC tumorigenesis, and verifying their potential as targets for GBC targeted therapy. As a member of the MAPK family of signal transduction molecules, ERK1/2 is involved in the process of cell growth, proliferation and differentiation.…”
Section: A B C Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…COX-2 and p-ERK1/2 expression were found to be markedly lower in normal gallbladder tissues than in GBC tissues, and their expression levels were also lower in HIBEpiC cells than in GBC-SD and NOZ cells. These results were consistent with previous studies (9)(10)(11), indicating that aberrant COX-2 and ERK1/2 activation may serve key roles in GBC tumorigenesis, and verifying their potential as targets for GBC targeted therapy. As a member of the MAPK family of signal transduction molecules, ERK1/2 is involved in the process of cell growth, proliferation and differentiation.…”
Section: A B C Discussionsupporting
confidence: 93%
“…Extracellular signal-regulated kinase 1/2 (ERK1/2) is a member of the mitogen-activated protein (10,11), and that aberrant ERK1/2 activation is closely associated with tumorigenesis and progression in various tumor types (12,13). It has also been demonstrated that COX-2 and ERK1/2 may serve as potential therapeutic targets for certain tumors, and their specific inhibitors have shown encouraging outcomes for cancer patients (14).…”
Section: Introductionmentioning
confidence: 99%
“…CDX2 has been identified by Yamamoto et al 27 as a protein able to bind to the MUC2 promoter and initiate transcription, and subsequent studies by Mesquita et al have shown two functionally active CDX2-binding sites. 26 Ectopic expression of CDX2 has also been linked to MUC2 expression in gastric intestinal metaplasia, 69 Barrett's esophagus, 70 and cholangiocarcinoma, 71 suggesting an important regulatory role for CDX2 in MUC2 expression. We and others have reported that CDX2 may be somatically lost in some colorectal cancers either due to out-offrame allelic gains or losses of the microsatellite repeat within the CDX2-coding region, 29,72 epigenetic silencing via methylation, 73 or loss of heterozygosity.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of pERK1/2 protein was seen in 49.2% of CCA cases. 34) ERKs can be activated by several stimuli including growth factors, cytokines and carcinogens. The ERK phosphorylation cascade is linked to cell surface receptor tyrosine kinases (RTKs) and other upstream signaling proteins with known oncogenic potential such as EGFR and human EGF receptor 2 (HER2) which are overexpressed in CCA.…”
Section: )mentioning
confidence: 99%